This too is music - Upitis, Rena 1985- (Oxford scholarship online, 2019)
'This Too is Music' inspires teachers to foster playful settings where young students can thrive as improvisers, critical listeners, performers, and composers. Told through anecdotes and illustrated with examples, the book quells any doubts teachers may have regarding their abilities to create an environment where children can grow as musicians